A review of universal-service policy - Lars Hultkrantz (Örebro University School of Business, 2005)
In some countries, like Sweden, regulatory reform of monopoly industries such as telecom and mail went ahead without much consideration to how competition would affect the universal provision of services. This paper reviews issues that ought to be considered in the process of shaping a universal-service policy that is conform to market competition.
Keywords: L51; L87; L90; 330; auctions; regulation; telecom; rail; mail